The organization of foreign language teaching material on the grounds of questioning system - Chvasas , M.; Velička , A. (Psichologija, 1973)
In teaching foreign languages, methodical units are linguistic images – sentences, which are modelled according to the purpose of the sentence; the sentence is formed according to the question which it needs to address. In “Teaching map” the whole teaching material focuses on the question (lexicon and grammar) which aids in forming the question and the answer to it. While working with such maps the student is freed from memorizing of certain information (definitions, terms, classification etc.) which he acquires at different times and from different sources (morphology, syntax, lexicology etc.), but which is currently not necessary to this student.
Keywords: teaching foreign languages; teaching map